On the (in)stability of nonlinear feedback solutions in a dynamic duopoly with renewable resource exploitation - Luca Lambertini; Andrea Mantovani (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2016)
We revisit Fujiwaraís (2008) differential duopoly game to show that the degenerate nonlinear feedback identified by the tangency point with the stationary state line is indeed unstable, given the dynamics of the natural resource exploited by firms. To do so, we fully characterise the continuum of nonlinear feedback solution via Rowat's (2007)method, characterising the infinitely many stable nonlinear feedback equilibria.
Keywords: C73; L13; Q2; 330